2011
DOI: 10.1021/bi2002136
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Arrest by a G Quadruplex Forming-Trinucleotide Repeat Sequence from the Human c-myb Gene

Abstract: Non canonical DNA structures correspond to genomic regions particularly susceptible to genetic instability. The transcription process facilitates formation of these structures and plays a major role in generating the instability associated with these genomic sites. However, little is known about how non canonical structures are processed when encountered by an elongating RNA polymerase. Here we have studied the behavior of T7 RNA polymerase (T7RNAP) when encountering a G quadruplex forming-(GGA)(4) repeat loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 38 publications
3
60
0
Order By: Relevance
“…G-quadruplex structure in a DNA strand impairs translocation of motor protein (29). In particular, it arrests RNA polymerase when it forms on the template strand (30). We modified the plasmid to have an SP6 promoter downstream of the T7 terminator and an SP6 terminator upstream of the T7 promoter (Figure 1C, scheme).…”
Section: Resultsmentioning
confidence: 99%
“…G-quadruplex structure in a DNA strand impairs translocation of motor protein (29). In particular, it arrests RNA polymerase when it forms on the template strand (30). We modified the plasmid to have an SP6 promoter downstream of the T7 terminator and an SP6 terminator upstream of the T7 promoter (Figure 1C, scheme).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that the formation of non-canonical structures, such as a G-quadruplex, reduce transcription efficiency because these structure induce pausing of the polymerase (42,43). For a template, we used a cholesterol-conjugated DNA with a G-quadruplex forming region near the 5â€Č end (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Enthalpy–entropy compensation plot for the folding thermodynamics of ( A ) mcG n G-quadruplexes in the presence of POPC liposome and ( B ) G-quadruplexes in the absence of liposome (18,42,43). …”
Section: Discussionmentioning
confidence: 99%
“…However, alternative DNA secondary structures, such as the G4 quadruplex, arrest transcription when they are formed in the non-transcribed strand. 12,13 Some types of damage, including the DNA adducts of aristocholic acid and the monofunctional adducts formed by irofulven (6-hydroxymethylacylfulvene), are transparent to recognition by the GGR pathway, but they can be sensitively detected by translocating RNAP, resulting in their efficient repair by TCR. 14,15 Of course, only the transcribed strands of expressed genes are being repaired in these cases; mutation-generating lesions persist in most of the genome.…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%